2018
DOI: 10.1007/s10067-018-4238-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and feasibility of the multidisciplinary management of patients with psoriatic arthritis: two-year clinical experience of a dermo-rheumatologic clinic

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory autoimmune arthritis, occurring in patients with psoriasis (Pso), that may affect the whole musculoskeletal system but also nails, eye, and gastrointestinal tract. Dermatologists and rheumatologists usually manage Pso and PsA separately, but early diagnosis and integrated management could achieve better outcomes of both skin and musculoskeletal manifestations, thus improving the health-related quality of life (HRQoL) of patients. In this work, we have describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 40 publications
3
54
0
1
Order By: Relevance
“…Furthermore, studies have demonstrated that patients managed in a multidisciplinary manner by both dermatologists and rheumatologists show improvements in disease activity and quality of life. 21,22 Our results suggest a need for a rheumatologist-dermatologist collaborative approach to optimize management of patients with PsA.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, studies have demonstrated that patients managed in a multidisciplinary manner by both dermatologists and rheumatologists show improvements in disease activity and quality of life. 21,22 Our results suggest a need for a rheumatologist-dermatologist collaborative approach to optimize management of patients with PsA.…”
Section: Discussionmentioning
confidence: 81%
“…The aim of our PPAC is to (a) improve patient's journey in the Greek medical system; (b) provide early diagnosis of PsA in Pso patients; (c) recognize signs of Pso in undiagnosed seronegative arthritis patients; and (d) improve management of these complex disorders in patients that require multidisciplinary approach. Our model shares common characteristics with other combined clinics worldwide, all demonstrating the benefits of these collaborations (Cobo‐Ibáñez et al, 2016; Haberman et al, 2018; Luchetti et al, 2018; Velez et al, 2012).…”
Section: Methodsmentioning
confidence: 70%
“…Differential diagnosis is difficult and early management of PsA significantly improves the loss of function and quality of life of patients, as well as achieve control of the structural changes of bone and cartilage (Nystad, Husum, Furnes, & Fevang, 2018) There are several reports underlying the delay between development of PsA symptoms and diagnosis, which usually leads to various orthopedic, surgical operations, before actually these patients receive the right therapeutic agent (Nystad et al, 2018; Strauss et al, 2008). Previous studies also suggest that there are remarkable deviations in clinical handling and follow‐up of Pso and PsA patients, depending on the specialist they choose to initially see, and this often leads to misdiagnosis and loss of compliance (Cobo‐Ibáñez et al, 2016; Luchetti et al, 2018; Yélamos, Ros, & Puig, 2015). The previous problems are prevented using the PPAC pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These perceptions are in accord with recent studies indicating that PsO and PsA multidisciplinary units may facilitate early diagnosis of these conditions, offer a more comprehensive treatment approach and timely treatment initiation, and increase patient satisfaction and quality of life. [21][22][23] Similarly, patients with IBD exposed to a multidisciplinary IBD clinic may have lower rates of IBD-related hospitalization, lower odds of corticosteroid dependence, and lower risk of IBD-related surgeries as compared with patients under standard practice. 24 In addition to the clinical impact of IMIDs on patients in terms of physical suffering, impaired function, and diminished quality of life, these conditions have a significant economic impact on both the individual patient and society as a whole.…”
Section: (3-7)mentioning
confidence: 99%